Defining Belarusian Tourists’ Segment by the Example of Vilnius as their Destination - Yanachkina, Nadzeya; Mačerinskienė, Aida (Ekonomika, 2015)
The paper is devoted to the analysis of the Belarusian tourist market on the example of Vilnius as a tourism destination. The main objectives of the article are: 1) to identify the dynamics of inbound tourist arrivals from Belarus to Lithuania for 2008–2013 and 2) to define preferences of tourists from Belarus and the main target audience on the Belarusian tourist market. The research has been conducted using such methods as secondary statistical data analysis of the main inbound tourism indicators and a survey using an online questionnaire. The paper has revealed that tourist arrivals from Belarus to Lithuania have been constantly growing, making up 1,045 million in 2013, which corresponds to 19.8% of all tourists that visited Lithuania that year. The empirical research has also found out that the prospective consumer of tourist services provided in Vilnius is a Belarusian aged 26–45, married, employed, with the average monthly income 501–1000 euro, has children, has been to Vilnius more than 4 times, prefers individual travelling, usually travels with family, visits Vilnius for shopping, events, excursions and transit purposes, stays in Vilnius for 2 days and spends about 340 euro. Taking into consideration the mentioned facts, the paper concludes that the development of marketing activities specifically tailored to the needs of Belarusian tourists will help to increase tourist arrivals and tourists’ expenses.
Keywords: destination; tourist arrivals; tourism destination marketing; tourist market